2004
DOI: 10.1161/01.cir.0000141574.78032.a9
|View full text |Cite
|
Sign up to set email alerts
|

Improved Vascular Gene Transfer With a Helper-Dependent Adenoviral Vector

Abstract: Background— Adenoviral vectors are the most widely used agents for vascular gene transfer. However, the utility of adenoviral vectors for vascular gene transfer is limited by brevity of expression and by the induction of a significant host inflammatory response. Third-generation or “helper-dependent” adenoviral vectors have achieved prolonged recombinant gene expression in liver and muscle with minimal associated inflammation; however, they have never been tested for vascular gene tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 53 publications
3
16
0
Order By: Relevance
“…4447 Despite these impressive results, there are several reasons why neither of these approaches has advanced to the clinic: 1) systemic injection of large amounts of viral vectors is toxic; 48 2) transgene expression is gradually lost after hepatocyte gene transfer, likely due to cell turnover; 49 3) in humans, even the most advanced approaches to hepatocyte gene transfer require immunosuppression to maintain transgene expression; 50 and 4) the risks to patient well-being of radiation and bone-marrow transplantation outweigh the potential benefits of slowing atherosclerosis progression. The approach used in the present study has the potential to avoid all of these limitations because local infusion of HDAd to the artery wall is minimally toxic, 51 yields transgene expression that appears to last indefinitely (without immunosuppression), 33 does not require marrow-ablative chemotherapy, and has a minimal risk of genotoxicity due to use of adenovirus, a non-integrating vector. Moreover, transduction of vascular cells—predominantly endothelial cells in this model 3739 —delivers lipid-poor apo A-I directly to the site of atherosclerotic disease.…”
Section: Discussionmentioning
confidence: 99%
“…4447 Despite these impressive results, there are several reasons why neither of these approaches has advanced to the clinic: 1) systemic injection of large amounts of viral vectors is toxic; 48 2) transgene expression is gradually lost after hepatocyte gene transfer, likely due to cell turnover; 49 3) in humans, even the most advanced approaches to hepatocyte gene transfer require immunosuppression to maintain transgene expression; 50 and 4) the risks to patient well-being of radiation and bone-marrow transplantation outweigh the potential benefits of slowing atherosclerosis progression. The approach used in the present study has the potential to avoid all of these limitations because local infusion of HDAd to the artery wall is minimally toxic, 51 yields transgene expression that appears to last indefinitely (without immunosuppression), 33 does not require marrow-ablative chemotherapy, and has a minimal risk of genotoxicity due to use of adenovirus, a non-integrating vector. Moreover, transduction of vascular cells—predominantly endothelial cells in this model 3739 —delivers lipid-poor apo A-I directly to the site of atherosclerotic disease.…”
Section: Discussionmentioning
confidence: 99%
“…FGAduPA, FGAdNull, and FGAdCMVnlacZ are first-generation E1/E3-deleted vectors that contain a rabbit urokinase plasminogen activator (uPA) cDNA, 18 an identical expression cassette without the uPA transgene, 18 and a nucleus-localized β-galactosidase gene, 19 respectively. HDAduPA, 15 HDAdNull 20 and HDAdGFP 20 are helper-dependent vectors, lacking all viral open reading frames. HDAduPA and HDAdNull contain the same expression cassettes as FGAduPA and FGAdNull, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…HDAd expressed a transgene far longer than first-generation (FG) Ad (≥ 8 wk versus 1 – 2 wk for FGAd) 5, 6 and caused only minimal vascular inflammation. 15 These data were promising and suggested that HDAd will be broadly useful for both investigational and therapeutic purposes. However, atherosclerosis and other vascular diseases develop and progress on a background of hyperlipidemia and associated arterial pathology.…”
mentioning
confidence: 97%
“…These viruses have an increased cloning capacity of approximately 35 kb (compared to around 8 kb in first- and second-generation viruses) and produce no viral proteins in infected cells [54], as a result of which they give rise to markedly reduced host adaptive immune responses and longer durations of transgene expression [55]. These helper-dependent (or “gutless” if you prefer the more colourful nomenclature) vectors have been applied to gene transfer within the vasculature of animals with impressive medium-term results [56,57]. Transgene expression persisted for at least eight weeks in rabbit carotids infected with a helper-dependent adenovirus expressing rabbit urokinase-type plasminogen activator, with stable expression from day 14 to day 56, which contrasted with complete loss of transgene expression by day 14 from arteries infected with first-generation viruses.…”
Section: Virus Vectors For Cardiovascular Gene Transfermentioning
confidence: 99%
“…Most such pre-clinical studies are of a relatively short-term nature and it seems that the advantages in duration of transgene expression and reduced host inflammatory responses that are offered by gutless adenoviruses do not outweigh the extra effort of manufacture, particularly as Wen et al reported that peak transgene expression following helper-dependent virus-mediated gene transfer was only around 10% of that observed after a first-generation virus was used to deliver the same transgene [57]. In addition, gutless adenoviruses still induce an innate immune response to the viral caspid [61] (and possibly to CpG motifs within the viral genome itself [6264]) and most adult humans still possess pre-existing antibodies to the serotype 5 virus particles: the absence of viral protein expression does not confer any greater capacity to evade pre-existing humoral immunity [57]. Until the advantages that third-generation adenoviruses undoubtedly possess in immunologically naïve experimental animals are shown to translate into clinical benefits by comparison to first-generation adenoviruses, it is likely that researchers will persevere with the old technology.…”
Section: Virus Vectors For Cardiovascular Gene Transfermentioning
confidence: 99%